Hemodynamic Changes After Intubation of Endotracheal Tube, LMA Classic™, and I-gel in Patients Candidates for Elective Eye Surgery - Akhondzadeh, Reza; Vojdani, Salman; Aslani, Seyed Mehdi (Annals of Anesthesiology and Critical Care, 2018)
Background: One of the concerns of the anesthetists in performing surgical procedures is hemodynamic changes after laryngoscopy and tracheal tube intubation. In these cases, stress response with the release of catecholamines leads to increased blood pressure and heart rate in patientswhoare prone to cardiovascular disease and cerebral events, leading to the life-threatening risks. Objectives: Endotracheal Intubation (ETT) is one of the most stress response techniques for airway management. Here, wecompare the effects of tree devices including ETT, laryngeal mask airway (LMA) classic, and I-gel with each other. Methods: The present study investigated the hemodynamic changes in patients undergoing elective cataract surgery after the intubation of an endotracheal tube. This clinical trial study was conducted on 75 patients with ASA class I or II in both genders and in the age group of 50 - 65 years old. The effects of LMA Classic™ and I-gel were also investigated. In this study, patients’ vital signs such as pulse rate, systolic blood pressure, and diastolic blood pressure were measured and recorded at times before insertion of the airway devices, one, two, and five minutes after the insertion. Results and Conclusions: Before the start of the operation, there was no significant difference between the groups in terms of hemodynamic parameters. Immediately before inserting ETT, LMA, or I-gel, the heart rate and systolic and diastolic blood pressure increased significantly in all groups. Our results generally showed that the hemodynamic changes due to the I-gel insertion compared to the tracheal tube and LMA Classic™ insertion followed minor adjustments. In a comparison between the insertion of the endotracheal tube and LMA Classic™, the use of the LMA Classic™ was associated with more stability